Model konstruktivisme pada pembelajaran IPS berbasis pembelajaran abad 21 di Madrasah Ibtidaiyah - Wardah, Nazhiifa Asyila; Ikhtiono, Gunawan; Andestend (Program Studi Magister Pendidikan Agama Islam, 2024)
Based on observations at Madrasah Ibtidaiyah Swasta (MIS) Nurul Yaqin, there are still some students who are less active during learning so teaching and learning activities tend to be monotonous, this can be seen from the learning outcomes of students in certain materials are below the minimum completeness criteria that have been applied, namely 70. This study aims to examine the effect of constructivism models based on 21st-century learning in improving student learning outcomes in social studies learning. In this study, researchers used quantitative methods using a quasi-experimental approach. The results showed that the calculation of the independent t-test of the experimental class found that the t-count result was -11.696 with (df) frequency data (n-1) which is 59-1 with a result of 58. The decision was taken based on the two-way significance value sig. (2-tailed) of 0.00, which is below the 0.05 threshold. A significance value smaller than 0.05 identifies the acceptance of the alternative hypothesis (Ha), which means there is a significant difference between the average pre-test and post-test scores. Normality test uses Test Of Normality with Kolmogorov-Smirnov test, using Test of Homogeneity of Variance to test homogeneity and independent t-test for hypothesis testing. The calculation was processed using the IBM SPSS 26 statistict application for windows.Results Based on the calculation of independent samples t-test, the sig. (2-tailed) value obtained is 0.00, lower than 0.05. This indicates that the proposed hypothesis can be accepted. Therefore, teachers should apply active, innovative and fun learning models in learning activities so that students are not bored in learning and can improve their understanding in achieving learning goals. Keywords: Constructivism; Learning outcomes; Student understanding Abstrak Berdasarkan hasil pengamatan di MIS Nurul Yaqin, masih terdapat beberapa siswa yang selama belajar kurang aktif sehingga kegiatan belajar mengajar cenderung monoton, hal ini terlihat dari hasil belajar siswa dalam materi tertentu berada di bawah kriteria ketuntasan minimum yang telah diterapkan yaitu 70. Penelitian ini bertujuan untuk menguji pengaruh dari model konstruktivisme berbasis pembelajaran abad 21 dalam meningkatkan hasil belajar siswa pada pembelajaran IPS. Pada penelitian ini peneliti menggunakan metode kuantitatif dengan menggunakan pendekatan quasi eksperimen. Hasil penelitian menunjukkan bahwa perhitungan independent-t test kelas eksperimen ditemukan bahwa hasil t-hitung -11,696 dengan (df) data frekuensi (n-1) yaitu 59-1 dengan menghasilkan 58. Keputusan diambil berdasarkan nilai signifikansi dua arah sig.(2-tailed) sebesar 0,00, yang berada di bawah ambang batas 0,05. Nilai signifikansi yang lebih kecil dari 0,05 mengidentifikasikan penerimaan hipotesis alternatif (Ha), yang berarti terdapat perbedaan signifikan antara rata-rata skor pre-test dan post-test. Uji Normalitas menggunakan Test of Normality dengan uji Kolmogorov-smirno, menggunakan Test of Homogeneity of Variance untuk menguji homogenitas dan independendt-t test untuk uji hipotesis. Perhitungan tersebut diolah dengan menggunakan aplikasi IBM SPSS 26 statistict for windows. Hasil Berdasarkan perhitungan independent samples t-test nilai sig.(2-tailed) yang diperoleh adalah 0,00, lebih rendah dari 0,05. Hal ini mengindikasikan bahwa hipotesis yang diajukan dapat diterima. Maka dari itu guru sebaiknya dalam kegiatan pembelajaran menerapkan model pembelajaran yang aktif, inovatif dan menyenangkan agar siswa tidak jenuh dalam belajar dan dapat meningkatkan pemahamannya dalam mencapai tujuan pembelajaran.